IgG4-related periaortitis/periarteritis: An under-recognized condition that is potentially life-threatening - Mizushima, Ichiro; Kasashima, Satomi; Fujinaga, Yasunari; Kawano, Mitsuhiro; Ishizaka, Nobukazu (Modern rheumatology, 2019)
Periaortitis and periarteritis are one of the clinical features of IgG4-related disease. Such vascular manifestations are reported to be present in 10-30% of overall IgG4-related disease, and they may also appear as an isolated lesion of IgG4-related disease. As other types of large vessel vasculitis, IgG4-related vasculitis may cause significant clinical consequences. On the other hand, the diagnosis of IgG4-related periaortitis/periarteritis seems to have been made on the basis of different diagnostic criteria in reported studies; thus far, difficulty seems to be present in assessing the true frequency of the disease as well as determining the optimal therapeutic strategy. In this review, in addition presenting the clinical and pathological features of IgG4-related periaortitis/periarteirtis, we would like to discuss on what kind of points should be resolved for the better understanding of vascular involvement of IgG4-related disease in terms of diagnosis and treatment.